2017
DOI: 10.1159/000480351
|View full text |Cite
|
Sign up to set email alerts
|

Can Early Dissection of Cervical Lymph Nodes Improve Prognosis in Squamous Cell Carcinomas of the Hard Palate

Abstract: Squamous cell carcinomas of the hard palate and maxillary alveolar ridge are rare tumours with a poor prognosis. Lymph node dissection is recommended for tumours with nodal involvement, and is rarely performed in the absence of adenopathy. We report a series of patients with squamous cell carcinomas and evaluate the rate of lymph node invasion and its impact on survival. This is a retrospective study of 72 patients treated for squamous cell carcinoma of the hard palate and maxillary alveolar ridge between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In tongue and laryngopharyngeal cancers, advanced stage of the disease signifies poor prognosis. Nevertheless, studies have also shown a subset of early stage patients that have an extremely poor prognosis [65,66]. Biomarkers that can further classify these patients based on outcome can be immensely valuable in this context.…”
Section: Discussionmentioning
confidence: 99%
“…In tongue and laryngopharyngeal cancers, advanced stage of the disease signifies poor prognosis. Nevertheless, studies have also shown a subset of early stage patients that have an extremely poor prognosis [65,66]. Biomarkers that can further classify these patients based on outcome can be immensely valuable in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, among SCC of the oral cavity, maxillary carcinomas do present some features to take into account when deciding the treatment protocol: (i) their lymphatic drainage path is different from that of other tumors located elsewhere in the oral mucosa; (ii) their global percentage of occult metastases is close to that of other SCCs in the oral cavity; (iii) like any other tumor location in Deneuve 11 Note: Data from the selected articles regarding the location of cervical metastases in maxillary SCC, dividing the locations of the neck according to the levels defined by the AJCC.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tumors located in the HPUGAR, studies in the USA, Canada, and France have reported incidence rates of 57.1%, 56%, and 65.3%, respectively. 16,31,32 Tumors with an advanced T stage make the surgical treatment much more aggressive, even though surgery alone remains the gold standard.…”
Section: Discussionmentioning
confidence: 99%